1998
DOI: 10.1002/(sici)1096-9861(19980105)390:1<41::aid-cne4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-concentrating hormone system in the brain of the lungfishProtopterus annectens

Abstract: The neurochemical anatomy of the lungfish brain is of particular interest, because many features in these animals might be representative of the common ancestor of land vertebrates. In the present study, we have investigated the localization and biochemical characteristics of melanin-concentrating hormone (MCH)-immunoreactive material in the central nervous system of the African lungfish, Protopterus annectens. The most prominent group of MCH-immunoreactive cell bodies was found in the dorsal hypothalamus. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…There is considerable evidence indicating the existence of a strong evolutionary pressure that acted to conserve the sequence of the biologically active domain of MCH (Vallarino et al 1998). It has been shown that rat and human MCH are identical (Nahon et al 1989;Vaughan et al 1989;Presse et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is considerable evidence indicating the existence of a strong evolutionary pressure that acted to conserve the sequence of the biologically active domain of MCH (Vallarino et al 1998). It has been shown that rat and human MCH are identical (Nahon et al 1989;Vaughan et al 1989;Presse et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, eel MCH and salmon MCH differ by only one substitution (Asn vs Asp) located outside the ring structure that corresponds to the biologically active domain of the peptide (Kawauchi et al 1983(Kawauchi et al , 1993. In the cyclic region of the molecule, mammalian and salmonid MCH exhibit only one conservative substitution (Leu vs Val) (Vallarino et al 1998). All these data and the absence of MCH immunoreactivity in the preadsorption tests (with rat MCH and salmon MCH) strongly suggest the specificity of rat MCH in recognizing Cichlasoma MCH not only in the brain and pituitary gland but also in skin neuromasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, the biological effect of MSH on skin pigmentation was studied extensively in vertebrates (Bunel et al, 1992;Vallarino et al, 1998;Jegou et al, 1993). Colocalization of α-MSH and MCH has been reported in the dorsolateral hypothalamic region of the rat (Naito et al, 1986;Fellman et al, 1987), in the preoptic nucleus of the frog, Rana ridibunda (Andersen et al, 1987), and in the nucleus sacci vasculosi in the brain of the dogfish, Scyliorhinus canicula (Vallarino et al, 1989) and lungfish, Protopterus annectens (Vallarino et al, 1998) and cichlid fish Cichlasoma dimerus (Pandolfi et al, 2003).…”
Section: The Distribution Of α-Msh-irmentioning
confidence: 99%